Complete Genome Sequence of pAP13, a Large Linear Plasmid of a Brevibacterium Strain Isolated from a Saline Lake at 4,200 Meters above Sea Level in Argentina - Dib, Julian Rafael (2013)
pAP13 is an 89 kb-linear plasmid hosted by Brevibacterium sp. Ap13, an actinobacterium isolated from the feces of a flamingo from an extremely high-altitude lake in Argentina. Because of the ecological importance of the genus Brevibacterium, the absolute lack of information concerning Brevibacterium linear plasmids, as well as the as the possible ecological significance of this unusual plasmid, pAP13 was completely sequenced, including the inversely oriented termini.